Molecular and immunohistochemical testing of bone tumours: review and update. Issue 6 (16th December 2022) - Kovacs, S Krisztian; Manassaporn, Atikankul; Nielsen, G Petur; Hung, Yin P
Abstract : Primary bone tumours can pose diagnostic problems due to their overlapping radiologic and histologic features. Given the recent advancement in our understanding of the biology of bone tumours, multiple immunohistochemical and molecular markers have been devised to aid in their diagnosis. This review provides brief updates on select bone tumours, including chondrosarcomas, benign chondrogenic tumours, osteosarcomas, benign osteogenic tumours, fibroosseous lesions, vascular tumours, osteoclastic giant cell‐rich or cystic tumours, chordoma, adamantinoma, small round blue cell sarcomas, and others. We discuss their salient molecular features and novel immunohistochemical correlates, along with some tips to avoid common diagnostic pitfalls. Abstract : Review of molecular features and immunohistochemical correlates in bone tumours.